Flesh made word: saints' stories and the western imagination - Kleinberg, Aviad M. (Belknap Press of Harvard University Press, 2008)
Sanctity -- The beginnings -- On the way to heaven : Perpetua's passion -- The ascetics -- Antony, the first hermit -- The ascetic pendulum -- Paul, an ascetic in paradise -- Suspended between heaven and earth : Simeon stylites -- Saints' stories and the rise of a popular literature -- Francis of Assisi, a joyful ascetic -- Fra Ginepro, the holy fool -- The golden legend